2019
DOI: 10.1186/s12864-019-5731-0
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplexes may determine the landscape of recombination in HSV-1

Abstract: Background Several lines of evidence suggest that recombination plays a central role in replication and evolution of herpes simplex virus-1 (HSV-1). G-quadruplex (G4)-motifs have been linked to recombination events in human and microbial genomes, but their role in recombination has not been studied in DNA viruses. Results The availability of near full-length sequences from 40 HSV-1 recombinant strains with exact position of the recombination breakpoints provided us with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…16 Bioinformatics and the following experimental analysis traced conserved PQSs in: (i) the promoter region of immediate-early genes of all alpha-HHVs, genes that are expressed at the very early stage of viral infection and encode for regulatory proteins involved in all subsequent viral steps 17 (ii) the terminal and internal repeated regions, which include packaging signals involved in concatemer cleavage during replication 13 (iii) the proximity of recombination breakpoints. 18 Most of the identified G4s proved to be exceptionally stable when tested in vitro through biochemical and biophysical assays.…”
Section: Alpha-herpesvirusesmentioning
confidence: 97%
“…16 Bioinformatics and the following experimental analysis traced conserved PQSs in: (i) the promoter region of immediate-early genes of all alpha-HHVs, genes that are expressed at the very early stage of viral infection and encode for regulatory proteins involved in all subsequent viral steps 17 (ii) the terminal and internal repeated regions, which include packaging signals involved in concatemer cleavage during replication 13 (iii) the proximity of recombination breakpoints. 18 Most of the identified G4s proved to be exceptionally stable when tested in vitro through biochemical and biophysical assays.…”
Section: Alpha-herpesvirusesmentioning
confidence: 97%
“…The terminal guanosine of G4 clusters at the boundaries of unique long (U L ) region represent the most common breakpoint among the HSV-1 recombinants. 133 On the basis of the accumulating evidence, G4s in these regions might play a role in the evolution of viruses, suggesting that RNA G4s are fundamental for the evolution of viruses.…”
Section: The Role Of G-quadruplex In Virologymentioning
confidence: 99%
“…The investigation of the G4-motifs in recombination among HSV-1 found that the PQS of the genome are enriched in recombination breakpoints and in regions flanking the recombination breakpoints. The terminal guanosine of G4 clusters at the boundaries of unique long (U L ) region represent the most common breakpoint among the HSV-1 recombinants . On the basis of the accumulating evidence, G4s in these regions might play a role in the evolution of viruses, suggesting that RNA G4s are fundamental for the evolution of viruses.…”
Section: The Role Of G-quadruplex In Virologymentioning
confidence: 99%
“…With the homology between the pac1 and pac1-like sequences, it seems likely that pac1-like could also form G-quadruplexes. A recent report highlighted the enrichment of G-quadruplexes in the regions flanking DNA breakpoints in HSV-1 and demonstrated that they are sites of recombination [51]. Additionally, reports that HSV-1 recombination factors such as ICP8 have been shown to co-localize with G-quadruplexes, and that UL12, an alkaline nuclease that binds the cellular double strand break-sensing MRN complex, co-localizes with ICP8 [52] suggest that G-quadruplexes may play a role in recruiting recombination machinery during herpesvirus DNA replication.…”
Section: Plos Pathogensmentioning
confidence: 99%